Biosynthesis of Ascorbic Acid as a Glucose-Induced Photoprotective Process in the Extremophilic Red Alga Galdieria partita - Fu, Han-Yi; Liu, Shao-Lun; Chiang, Yin-Ru (Frontiers in Microbiology, 2020)
The extremophilic red alga Galdieria partita is a facultative heterotroph that occupies mostly low-light microhabitats. However, the exceptional detection of abundant populations of G. partita in sunlight-exposed soil raises the possibility that exogenous organic carbon sources protect cells from photo-oxidative damage. The present study aimed to identify the photoprotective process activated by exogenous glucose under photo-oxidative stress. We demonstrated that exogenous glucose mitigated the photo-oxidative damage of cells exposed to 300 µmol photons m−2 s−1 photosynthetic active radiation. Photosynthesis carbon assimilation scarcely contributed to the cell growth in the presence of glucose, but the photosynthetic apparatus was nevertheless maintained and protected by glucose in a concentration-dependent manner. Supplementation of glucose increased expression of the L-gulonolactone oxidase gene essential for ascorbic acid biosynthesis, whereas no enhanced expression of the genes involved in carotenoid or tocopherol biosynthesis was observed. Under the photo-oxidative stress condition, the ascorbic acid content was strongly enhanced by exogenous glucose. We propose that the biosynthesis of ascorbic acid is one of the major photoprotective processes induced by exogenous glucose. The elucidation of how ascorbic acid is involved in scavenging reactive oxygen species provides key insights into the photoprotective mechanism in red algae.